Simulation of dynamics of the order parameter in superconducting nanostructured materials: Effect of the magnetic field renormalization; Low Temperature Physics; Vol. 46, iss. 4 - Smirnova E. I. Ekaterina Ivanovna (2020, 2020)
Title screen